The United States, Texas & the British Provinces of the Canadas, Newfoundland, Nova Scotia, N. Brunswick & Prince Edward Island. - Evans, William Gardner ([F.J. Huntington], 1838)
Map shows major cities, political divisions and geography of early nineteenth century North America. Relief shown by hachures. Scale [ca. 1:10,137,600].